2004
DOI: 10.1159/000082748
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aminopeptidase Activities in Rats after Left and Right Intrastriatal Administration of 6-Hydroxydopamine

Abstract: Asymmetries in the neuroendocrine system extend from central structures to paired endocrine glands and their innervation. In addition to the well-known asymmetry in the function of brain dopamine, there are also asymmetries in the peripheral response to experimental hemi-parkinsonism, performed by means of lesions of the nigrostriatal system with 6-hydroxydopamine (6-OHDA) injections into the left or right hemisphere. Therefore, it is speculated that the neuroendocrine system would also be asymmetrically affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
2
10
1
Order By: Relevance
“…They subsequently analyzed alanine-(AlaAP), cystine-(CysAP), aspartate-(AspAP) and glutamate-AP (GluAP) activities in plasma from PD patients, finding a significant decrease in all AP activities except for AlaAP [19] . Similar results were found in human brain [20] . We hypothesized that changes in AP activities during PD progression disturb the neuronal functions that they regulate.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…They subsequently analyzed alanine-(AlaAP), cystine-(CysAP), aspartate-(AspAP) and glutamate-AP (GluAP) activities in plasma from PD patients, finding a significant decrease in all AP activities except for AlaAP [19] . Similar results were found in human brain [20] . We hypothesized that changes in AP activities during PD progression disturb the neuronal functions that they regulate.…”
Section: Introductionsupporting
confidence: 89%
“…Moreover, AspAP activity was significantly higher in the ntPD group than in the control group, while CysAP activity was significantly lower in tPD than in the controls, in agreement with Banegas et al [19] . Other studies have reported AP activity changes in the striatum, SNPC, prefrontal cortex and plasma in animal models of PD [18,20] .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The samples used for DPPIV determination were also used for aminopeptidase enzyme activity determination. The enzymatic assay measured levels of 2-naphthylamine released as a result of aminopeptidase activity (1,29). Briefly, either 2 l of fasting lymph or 2 l of 2 ϫ diluted plasma was incubated with 100 l of 0.1 mg/ml L-tyrosine ␤-naphthylamide (Sigma) as the substrate in 50 mM HCl-Tris buffer (pH 7.6, Fisher Scientific, Fair Lawn, NJ) at 37°C for 2 h. The reaction was stopped by adding 100 l of 0.1 M acetate buffer (pH 4.2).…”
Section: Methodsmentioning
confidence: 99%